Telomere dysfunction and chromothripsis - Ernst, Aurélie; Jones, David T. W.; Maaß, Kendra K.; Rode, Agata; Deeg, Katharina; Jebaraj, Billy Michael Chelliah; Korshunov, Andrey; Hovestadt, Volker; Tainsky, Michael A.; Pajtler, Kristian Wilfried; Bender, Sebastian; Brabetz, Sebastian; et al. (International journal of cancer, 2016)
Chromothripsis is a recently discovered form of genomic instability, characterized by tens to hundreds of clustered DNA rearrangements resulting from a single dramatic event. Telomere dysfunction has been suggested to play a role in the initiation of this phenomenon, which occurs in a large number of tumor entities. Here, we show that telomere attrition can indeed lead to catastrophic genomic events, and that telomere patterns differ between cells analyzed before and after such genomic catastrophes. Telomere length and telomere stabilization mechanisms diverge between samples with and without chromothripsis in a given tumor subtype. Longitudinal analyses of the evolution of chromothriptic patterns identify either stable patterns between matched primary and relapsed tumors, or loss of the chromothriptic clone in the relapsed specimen. The absence of additional chromothriptic events occurring between the initial tumor and the relapsed tumor sample points to telomere stabilization after the initial chromothriptic event which prevents further shattering of the genome.